The cystic fibrosis lower airways microbial metagenome. Issue 2 (9th May 2016) - Moran Losada, Patricia; Chouvarine, Philippe; Dorda, Marie; Hedtfeld, Silke; Mielke, Samira; Schulz, Angela; Wiehlmann, Lutz; Tümmler, Burkhard
Chronic airway infections determine most morbidity in people with cystic fibrosis (CF). Herein, we present unbiased quantitative data about the frequency and abundance of DNA viruses, archaea, bacteria, moulds and fungi in CF lower airways. Induced sputa were collected on several occasions from children, adolescents and adults with CF. Deep sputum metagenome sequencing identified, on average, approximately 10 DNA viruses or fungi and several hundred bacterial taxa. The metagenome of a CF patient was typically found to be made up of an individual signature of multiple, lowly abundant species superimposed by few disease-associated pathogens, such as Pseudomonas aeruginosa and Staphylococcus aureus, as major components. The host-associated signatures ranged from inconspicuous polymicrobial communities in healthy subjects to low-complexity microbiomes dominated by the typical CF pathogens in patients with advanced lung disease. The DNA virus community in CF lungs mainly consisted of phages and occasionally of human pathogens, such as adeno- and herpesviruses. The S. aureus and P. aeruginosa populations were composed of one major and numerous minor clone types. The rare clones constitute a low copy genetic resource that could rapidly expand as a response to habitat alterations, such as antimicrobial chemotherapy or invasion of novel microbes. The CF lung metagenome is composed of few viruses and fungi and hundreds of bacterial species, clones and subclones http://ow.ly/ZiqUE